POLA MAKAN DAN PENGETAHUAN REMAJA PUTRI TENTANG KESEHATAN REPRODUKSI : GAMBARAN KERENTANAN FUNGSI REPRODUKSI DI MAN I SEMARANG - Eny Winaryati (JURNAL LITBANG, 2004)
The result of the research said that most of respondents (79,2 %), the students, girls, of MAN I Semarang consurned "Balancecl Nurition", that is, rice, side dish made from meat and fish, vegetables, fruit ancl milk. 80 % of sturlents consumed them three times a day and 100 % of then consumecl rice. Conceming ahout their knowledge about health and reproduction is described that 20% of thestudents (19 students) have good criteria in competence, and 50 % of them havi enough criteria.Meanwhile they received information concerning ahout sexiolog,, from their school mates, therefore, school officials such os teachers, coutrcilors etc. must guide ond council them properly. 76 % of the students had normal Hb level, 24 %, of them had little bit normul Hb let,el, thu is, less thun l3 grrm 9(t, thut they coultl suJfer front anemio, thus, rhey must tuke kthlet Fe.Keywords : Students of girl, consume puttern, Healt of reproduction